2011
DOI: 10.21091/mppa.2011.1002
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Research in Dance: A Literature Review

Abstract: The authors reviewed the literature, published from 1970 through December 2009, on biomechanical research in dance. To identify articles, the authors used search engines, including PubMed and Web of Science, five previous review articles, the Dance Medicine and Science Bibliography, and reference lists of theses, dissertations, and articles being reviewed. Any dance research articles (English language) involving the use of electromyography (EMG), forceplates, motion analysis using photography, cinematography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 14 publications
0
28
0
1
Order By: Relevance
“…The "grand plié" is not challenging for ballet dancers, however it is an essential basic ballet movement that is practiced daily from the very first lessons [21]. As a result of training, dancers develop specific motor strategies to achieve this movement, which are more effective than those of non-dancers [26]. The strategies developed depend on the type of dancing [16] and are not highlighted by non-dancingspecific balance tasks, such as the simple one leg stance [18].…”
Section: Discussionmentioning
confidence: 99%
“…The "grand plié" is not challenging for ballet dancers, however it is an essential basic ballet movement that is practiced daily from the very first lessons [21]. As a result of training, dancers develop specific motor strategies to achieve this movement, which are more effective than those of non-dancers [26]. The strategies developed depend on the type of dancing [16] and are not highlighted by non-dancingspecific balance tasks, such as the simple one leg stance [18].…”
Section: Discussionmentioning
confidence: 99%
“…During performance, ballet dancers have a great need for stability and balance control [1,2], along with a high level of general "flexibility", which are peculiar characteristics that improve with ballet training [1,[3][4][5]. Ankle control is of the utmost importance for executing static and dynamic positions typical of ballet dancing [6,7]. In 2017, Vassallo et al reported the epidemiology of dance-related injuries between 2000 and 2013, defining ankle sprains as the most common injury [8].…”
Section: Introductionmentioning
confidence: 99%
“…Articles in MPPA examining musical performance with EMG have included pianists, violinists, violists, cellists, and trumpeters, while its use in dance has included patellofemoral pain in ballet and grand battement devant. The use of EMG in music performance research was reviewed in a 2000 article by Kjelland, 3 and its use in dance was reviewed in a 2011 article 4 ; the lead author of that article was Donna Krasnow, who has just become MPPA's Associate Editor for Dance.…”
mentioning
confidence: 99%
“…W hat have we learned from articles that have used these diverse technologies to study health issues in performing artists? The review article by Krasnow et al 4 found:…”
mentioning
confidence: 99%
See 1 more Smart Citation